Desmodianone H and uncinanone B, potential tyrosinase inhibitors obtained from Lespedeza maximowiczii by using bioactivity-guided isolation. Issue 6 (3rd June 2014) - Heo, Do Yeon; Kim, Young Mi; Lee, Joongku; Park, Sang-Hong; Kim, Jinki; Park, Hye Min; Lee, Choong Hwan
Abstract: A new bioactive compound, namely desmodianone H (1), and another known compound uncinanone B (2) were first isolated using bioactivity-guided isolation from the leaves of Lespedeza maximowiczii and structures were elucidated by comprehensive analysis of their nuclear magnetic resonance and mass spectrometry data. Compounds 1 and 2 exhibited strong inhibitory effects on mushroom tyrosinase activity.